Cavendon Hall [compact disc, unabridged] - Bradford, Barbara Taylor, 1933- (Bradford, Barbara Taylor, 1933- Cavendon chronicles., 2014)
A sweeping, multi-generational saga set on the eve of WWI. Two entwined families: the aristocratic Inghams and the Swanns, who serve them. Cavendon Hall is a grand imposing house nestled in the beautiful Yorkshire Dales. But the year is 1913, and soon life as the two families of Cavendon Hall know it - Royal Ascot, supper dances, grouse season feasts - is about to change irrevocably.